Digital Hermeneutics and A New Face of The Qur`an Commentary: The Qur`an in Indonesian`s Facebook - Fadhli Lukman (Al-Jami'ah: Journal of Islamic Studies, 2018)
The 21st history of the Qur`an sees the scripture’s contiguity with the social media technology. This paper discusses the hermeneutical configuration of the Qur`an commentary in social media, not as religious phenomena in sociological or anthropological perspective, but rather as a study of the history of exegesis. The inquiry addresses two points: the character of the Qur’an commentary presented in Facebook within the context of the modern Qur’anic commentary and the effects it carries out. The paper suggests that digital hermeneutics emerges as the step forward for popularizing commentary with its simple and straightforward presentation. Accordingly, people are now closer to Qur`anic interpretation than ever before, and therefore the upsurge of semantic function of the Qur`an is observed. At the same time, digital hermeneutics marks the phenomena of equality and democratization of participation in hermeneutical activity and the challenge on authority.[Sejarah Al-Quran abad ke-21 ditandai dengan perkawinan kitab suci ini dengan teknologi sosial media. Paper ini mendiskusikan bangunan hermeneutis tafsir Al-Quran di sosial media, bukan sebagai fenomena keberagamaan dalam nuansa sosiologis dan antropologis, melainkan sebagai studi sejarah tafsir. Ada dua hal yang dikaji: tentang karakter tafsir Al-Quran yang muncul di Facebook dalam konteks tafsir modern dan pengaruh yang dimunculkannya. Diskusi ini menyimpulkan bahwa digital hermeneutics muncul sebagai kelanjutan dari tafsir populer dengan penampilannya yang sederhana dan lugas. Oleh sebab itu, orang-orang saat ini menjadi semakin dekat dengan penafsiran Al-Quran, dan meningkatnya fungsi semantik Al-Quran menjadi jelas terlihat. Pada saat yang sama, digital hermeneutics menandai kesetaraan dan demokratisasi dalam partisipasi terhadap aktivitas hermeneutis Al-Quran dan tantangan terhadap otoritas.]